2018
DOI: 10.1002/jsfa.9393
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of volatile profiles of green Hawai'ian coffee beans damaged by the coffee berry borer (Hypothenemus hampei)

Abstract: BACKGROUND The coffee berry borer (CBB), Hypothenemus hampei, is the most destructive insect pest of coffee globally, causing significant losses in yield and leading to ‘off’ flavors in damaged beans. Automated headspace sampling (AHS) and gas chromatography–mass spectrometry (GC–MS) were used to investigate changes in the volatile profiles of CBB‐damaged green coffee beans. Green coffee from three coffee farms on the island of Hawai'i were sorted into three levels of CBB damage: non‐damaged, slightly damaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(52 reference statements)
1
4
0
1
Order By: Relevance
“…In addition to environmental factors, this systematic review found that coffee quality is sensitive to shifts in management conditions. For example, simulated and actual pest infestation was found to increase various coffee quality parameters (Vaddadi and Parvatam, 2015;Walker et al, 2018). This trend is line with previous research on the upregulation of secondary metabolite defense compounds with herbivory (Scott et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In addition to environmental factors, this systematic review found that coffee quality is sensitive to shifts in management conditions. For example, simulated and actual pest infestation was found to increase various coffee quality parameters (Vaddadi and Parvatam, 2015;Walker et al, 2018). This trend is line with previous research on the upregulation of secondary metabolite defense compounds with herbivory (Scott et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…For example, the application of Rhizopus oligosporus and Aspergillus niger mycelial extracts as well as methyl jasmonate and salicylic acid resulted in increased levels of caffeine up to 42%, increased levels of theobromine up to 39%, increased levels of trigonelline up to 46%, and increased levels cafestol and kahweol up to 32% (Vaddadi and Parvatam, 2015). Walker et al (2018) found infestation by the coffee berry borer resulted in increased levels of key aromatic volatile metabolites often associated with off-flavors and aromas such as malty, green bean, and grassy attributes including the metabolites hexanal, 2-pentylfuran, 2-methylpropanal, 3-methylbutanal, 2methylbutanal, benzeneacetaldehyde, and nonanal.…”
Section: Pest and Disease Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…The aroma of coffee is intrinsically related to the chemical composition of the bean, genetic strain, geographical location, climate, annual rainfall, agricultural practice and processing method applied (Toledo et al, 2016;Buffo and Cardelli-Freire, 2004). In order to characterize the species and the influence of geographical origin, some studies are focused on the identification of volatiles in green coffee (Flament, 2001), fingerprinting coffee flavor (Huang et al, 2007), discrimination of volatiles in defective coffee (Toci and Farah, 2008;Walker et al, 2019) and the effect of climatic conditions on the volatile compounds of green coffee (Bertrand et al, 2012).…”
Section: Introductionmentioning
confidence: 99%